Vitamin D levels and left ventricular diastolic function. Issue 1 (17th February 2014) - Pandit, Anil; Mookadam, Farouk; Boddu, Sailaja; Aryal Pandit, Aashrayata; Tandar, Anwar; Chaliki, Hari; Cha, Stephen; Lee, Howard R
Abstract : Objective: To determine the association between serum vitamin D level and left ventricular (LV) diastolic dysfunction. Background: Vitamin D deficiency has been shown in observational and prospective studies to be associated with cardiovascular diseases including coronary artery disease, LV hypertrophy and systolic heart failure. Even though diastolic LV dysfunction is an early manifestation of cardiac disease, there is no study that examines whether a deficiency of vitamin D is associated with LV diastolic dysfunction. Method: A retrospective observational review of 1011 patients (679 women) was conducted to examine if low 25-OH-vitamin D levels were associated with LV diastolic dysfunction. Results: All the LV diastolic dysfunction parameters: left atrial volume index, E/e', e' velocity, LV mass index and deceleration time were not significantly different between patients with 25-OH vitamin D level ≤20 ng/mL vs 25-OH vitamin D level >20 ng/mL. Conclusions: Despite growing medical literature suggesting vitamin D deficiency is associated with cardiovascular disease, in this present study there is no significant association of vitamin D levels and LV diastolic performance, including left atrial volume index.